The Evaluation of Asset Pricing Models in Hong Kong Stock Market - Chen, Ruoxi (2012)
Asset pricing models play an important role in financial markets. Different asset pricing models take diverse factors into account. The study in this paper focus on the performance of different asset pricing models including the CAPM, the Fama and French (1993) three-factor model (FF3), the Fama and French (1993) five-factor model (FF5), the Kim (2006) two-factor model (K2), the Chen, Novy-Marx and Zhang (2010) three-factor model (C3), the CCAPM, the Campbell (1996) five-factor model (C5), and the Vassalou (2003) two-factor model (V2) in Hong Kong stock market in the period from 1992 to 2011. The time series regression, cross sectional regression, GRS F-tests, Hansen and Jagannathan (1997) distance, the Fama-MacBeth (1973) t-test and the Shanken (1992) errors in variables (EIV) corrected t-test are used in this paper. The result of this paper shows that the model FF5 and C3 work better than other models in Hong Kong stock market.